Risk factors for the increasing trend in low birth weight among live births born by vaginal delivery, Brazil Fatores de risco para a tendência ascendente do baixo peso ao nascer em nascidos vivos de parto vaginal no Sudeste do Brasil - Marco A Barbieri; Antônio AM Silva; Heloisa Bettiol; Uilho A Gomes (Universidade de São Paulo, 2000)
OBJECTIVE: To identify risk factors for low birth weight (LBW) among live births by vaginal delivery and to determine if the disappearance of the association between LBW and socioeconomic factors was due to confounding by cesarean section. METHODS: Data were obtained from two population-based cohorts of singleton live births in Ribeirão Preto, Southeastern Brazil. The first one comprised 4,698 newborns from June 1978 to May 1979 and the second included 1,399 infants born from May to August 1994. The risks for LBW were tested in a logistic model, including the interaction of the year of survey and all independent variables under analysis. RESULTS: The incidence of LBW among vaginal deliveries increased from 7.8% in 1978--79 to 10% in 1994. The risk was higher for: female or preterm infants; newborns of non-cohabiting mothers; newborns whose mothers had fewer prenatal visits or few years of education; first-born infants; and those who had smoking mothers. The interaction of the year of survey with gestational age indicated that the risk of LBW among preterm infants fell from 17.75 to 8.71 in 15 years. The mean birth weight decreased more significantly among newborns from qualified families, who also had the highest increase in preterm birth and non-cohabitation. CONCLUSIONS: LBW among vaginal deliveries increased mainly due to a rise in the proportion of preterm births and non-cohabiting mothers. The association between cesarean section and LBW tended to cover up socioeconomic differences in the likelihood of LBW. When vaginal deliveries were analyzed independently, these socioeconomic differences come up again. OBJETIVO: Identificar fatores de risco para o baixo peso ao nascer (BPN) entre nascidos vivos de parto vaginal e verificar se o desaparecimento da associação entre BPN e fatores socioeconômicos foi devido ao confundimento pela cesariana. MÉTODOS: Foram estudadas duas coortes de base populacional de recém-nascidos únicos de parto vaginal em Ribeirão Preto, Sudeste do Brasil. A primeira incluiu 4.698 crianças nascidas entre junho de 1978 e maio de 1979 e a segunda 1.399 crianças nascidas entre maio e agosto de 1994. Os riscos de BPN foram testados num modelo de regressão logística, incluindo interações entre ano da pesquisa e todas as variáveis independentes em análise. RESULTADOS: A incidência de BPN entre partos vaginais aumentou de 7,8% em 1978/79 para 10% em 1994 para crianças do sexo feminino, para os primogênitos, para nascidos de mães sem companheiro, para nascidos de mães que fizeram menor número de consultas pré-natais ou com menos anos de estudo e para nascidos de mães fumantes. A interação entre ano do parto e idade gestacional indicou que o risco de BPN entre os nascidos prematuros caiu de 17,8 para 8,7 em 15 anos. A média do peso ao nascer reduziu-se mais entre os filhos de famílias mais qualificadas, que tiveram o maior aumento nos nascimentos pré-termo e nas mães sem companheiro. CONCLUSÕES: O BPN entre partos vaginais aumentou principalmente devido ao incremento nos nascimentos pré-termo e nas mães sem companheiro. A associação entre cesariana e BPN tendeu a encobrir as diferenças socioeconômicas na probabilidade do BPN. Na análise dos partos vaginais isoladamente, as diferenças socioeconômicas reapareceram.